2024
DOI: 10.23822/eurannaci.1764-1489.280
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab to induce tolerance to SLIT-Melocotón®

Abstract: Introduction: Food allergy is an increasing problem for population and treatments inducing tolerance using sublingual immunotherapy is currently under study. Case presentation: Our aim as allergists is to achieve tolerance to sublingual allergen specific immunotherapy with sublingual immunotherapy (SLIT-peach). We present a case report consisting of a 40 year old woman with anaphylactic reactions after eating fruit and other plant-foods due to sensitization to nonspecific lipid transfer proteins (nsLTP). Her d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Dupilumab has been reported to resolve gastrointestinal symptoms that developed during omalizumab-facilitated oral immunotherapy [19]. Another case study has reported that dupilumab can help patients who have had anaphylaxis in response to omalizumab during sublingual immunotherapy for peach [20]. In line with these promising observations, there are several ongoing clinical trials investigating the use of dupilumab as an adjuvant for oral immunotherapy for peanut (NCT03682770) and milk (NCT04148352).…”
Section: Anti-il-4 Receptor Alphamentioning
confidence: 99%
“…Dupilumab has been reported to resolve gastrointestinal symptoms that developed during omalizumab-facilitated oral immunotherapy [19]. Another case study has reported that dupilumab can help patients who have had anaphylaxis in response to omalizumab during sublingual immunotherapy for peach [20]. In line with these promising observations, there are several ongoing clinical trials investigating the use of dupilumab as an adjuvant for oral immunotherapy for peanut (NCT03682770) and milk (NCT04148352).…”
Section: Anti-il-4 Receptor Alphamentioning
confidence: 99%